Impact of the Nationwide Intravenous Selenium Product Shortage on the Development of Selenium Deficiency in Infants Dependent on Long‐Term Parenteral Nutrition. (23rd February 2015) - Chen, Connie H.; Harris, Mary Beth; Partipilo, M. Luisa; Welch, Kathleen B.; Teitelbaum, Daniel H.; Blackmer, Allison B.
Abstract : Background : For patients dependent on parenteral nutrition (PN), selenium must be supplemented intravenously. A nationwide intravenous selenium shortage began in April 2011. The impact of this shortage on PN‐dependent infants was evaluated by examining the provision of selenium, development of biochemical deficiency, and costs associated with the shortage. Materials and Methods : This single‐center, retrospective study included PN‐dependent infants aged ≤1 year who weighed ≤30 kg, received PN for ≥1 month, and had ≥1 serum selenium measurement. The primary outcome was the incidence of biochemical selenium deficiency. Secondary outcomes included severity of biochemical deficiency, clinical manifestations, costs, and relationship between serum selenium levels and selenium dose. Results : The average selenium dose decreased 2‐fold during the shortage (2.1 ± 1.2 µg/kg/d; range, 0.2–4.6 µg/kg/d) versus the nonshortage period (3.8 ± 1 µg/kg/d; range, 2.4–6 µg/kg/d; P < .001). A linear relationship between serum selenium concentration and selenium dose was observed ( r 2 = 0.42), with a dose of 6 µg/kg/d expected to result in normal serum levels in most cases. Similar proportions of patients developed biochemical deficiency in both groups: shortage period, 59.1%; nonshortage, 66.7%; P = .13. The severity of biochemical deficiency was similar between groups. A significant increase in incremental cost during the shortage was observed. Conclusion : This is the first study examining the impact of the intravenous selenium shortage on PN‐dependent infants. Both groups exhibited similarly high incidences of biochemical selenium deficiency, suggesting higher empiric doses may benefit this population. However, ongoing shortages limit the ability to provide supplementation.